Epidemiology of Mycobacterium abscessus in England: an observational study - Lipworth, S; Hough, N; Weston, N; Chapman, S; Flight, W; Peto, T; Crook, D; Walker, AS; Eyre, D; Walker, T (Elsevier, 2021)
Background: Mycobacterium abscessus has emerged as a significant clinical concern following reports that it is readily transmissible in health-care settings between patients with cystic fibrosis. We linked routinely collected whole-genome sequencing and health-care usage data with the aim of investigating the extent to which such transmission explains acquisition in patients with and without cystic fibrosis in England.